2009
DOI: 10.1007/s11904-009-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of routine vaccination in HIV-infected persons

Abstract: Vaccine recommendations for those with HIV require continual updating as additional research becomes available. Timing of vaccinations among HIV-infected individuals is a key area of uncertainty. This is particularly true for those who may soon initiate highly active antiretroviral therapy (HAART) because immune reconstitution due to HAART often improves responses to vaccines. However, risks of delaying vaccination include that the patient may be exposed to the pathogen or lost to follow-up before vaccination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…However, persons on ART treatment had a more durable antibody response, both in magnitude and functional activity, following pneumococcal vaccination compared with ART-naïve subjects. 74,75 Further, some studies have observed a faster decline in IgG concentrations following pneumococcal conjugate vaccination among ART-naïve compared with ART-treated patients, 74 which could be secondary to increased turnover of memory B cells in untreated HIV-infected patients. 65 This effect of ART on vaccine responses cannot be explained by differences in CD4 þ T-cell count alone.…”
Section: B Cells and Immunoglobulinsmentioning
confidence: 99%
“…However, persons on ART treatment had a more durable antibody response, both in magnitude and functional activity, following pneumococcal vaccination compared with ART-naïve subjects. 74,75 Further, some studies have observed a faster decline in IgG concentrations following pneumococcal conjugate vaccination among ART-naïve compared with ART-treated patients, 74 which could be secondary to increased turnover of memory B cells in untreated HIV-infected patients. 65 This effect of ART on vaccine responses cannot be explained by differences in CD4 þ T-cell count alone.…”
Section: B Cells and Immunoglobulinsmentioning
confidence: 99%
“…Gli studi condotti al riguardo sono pochi e peraltro poco consistenti (17). Supposto che l'immuno-ricostituzione indotta dalla terapia aumenti l'efficacia del preparato vaccinale somministrato (20), la scelta di attendere una conta adeguata di linfociti T CD4 e una bassa viremia sembrerebbe quella più opportuna; d'altro canto, ogni vaccinazione procrastinata rappresenta una mancata opportunità di immunizzazione, per cui ci si assume il rischio di una potenziale esposizione o di perdita del paziente al follow-up (21,22). Un altro territorio di incertezza è quello relativo alla sicurezza dei preparati vaccinali.…”
Section: La Vaccinazione Nel Paziente Con Infezione Da Hivunclassified
“…48,57,59,67,112 The dangers of delaying vaccination include the risk of infection and the potential missed opportunity for vaccination due to lost follow-up. 117 In general, the administration of vaccines should occur at the initial HIV visit, or shortly thereafter in cases in which prevaccination testing is needed. For vaccines such as influenza, pneumococcal (with the conjugate vaccine), and hepatitis (A and B), administration should not be delayed since HIV-infected patients (even those with CD4 counts < 200 cells/mm 3 ) can develop adequate post-vaccination responses.…”
Section: Timing Of Vaccinationmentioning
confidence: 99%